2014
DOI: 10.1089/jpm.2013.0387
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion in Palliative Cancer Patients: A Review of the Literature

Abstract: Although transfusion is certainly a common practice in PCPs, there is a relative lack of literature on this topic. Publications are unconnected and hardly any prospective studies have been performed. A large part of the little literature available only concerns descriptive and very general aspects of the issue. As transfusional products and financial and human resources are finite, it would be desirable to establish clear research lines on the different aspects considered (clinical, infrastructure, and ethical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 49 publications
4
39
0
Order By: Relevance
“…35 However, the value of using predetermined Hb levels to determine need for transfusion in palliative care has not been studied. Similarly to a prior review, 36 we found that despite the lack of evidence-informed variables for transfusion in palliative care patients, Hb level remains the most common indication for transfusion in this population. The variation in practice observed in the current review suggests that the decision to transfuse was based largely on care providers' practice patterns rather than high-quality evidence.…”
Section: Discussionsupporting
confidence: 77%
“…35 However, the value of using predetermined Hb levels to determine need for transfusion in palliative care has not been studied. Similarly to a prior review, 36 we found that despite the lack of evidence-informed variables for transfusion in palliative care patients, Hb level remains the most common indication for transfusion in this population. The variation in practice observed in the current review suggests that the decision to transfuse was based largely on care providers' practice patterns rather than high-quality evidence.…”
Section: Discussionsupporting
confidence: 77%
“…According to our results, the GPs were more willing than the students to withhold blood transfusions, pleural drainage and chest X-rays in a patient scenario representing EOLcare. The benefit of blood transfusions in EOL-care is often brief and adverse effects may occur (15). Dyspnoea can sometimes be alleviated by pleural drainage, but the procedure is invasive (16).…”
Section: Discussionmentioning
confidence: 99%
“…32 Last, we must also study and explore models for providing end-of-life care for patients with hematologic malignancies that can overcome typical limitations of hospice care in the US, which fails to recognize the palliative benefits of supportive transfusions and palliative chemotherapies, as these are often not provided as part of hospice care because of reimbursement limitations. 31,46 …”
Section: Areas For Future Researchmentioning
confidence: 99%